The surgical management of osteoid osteoma: A systematic review - Shu, Man; Ke, Jin (Frontiers in Oncology, 2022)
Background: Osteoid osteoma (OO) comprises approximately 11%-14% of benign bone tumors. The main symptom of OO is localized pain accompanied by nighttime aggravation. Surgical treatment is frequently used in clinic, including open surgery and percutaneous ablation, the latter including radiofrequency ablation, cryoablation, and microwave ablation, but there is no consensus on when and how to choose the best treatment for OO. Purpose: We did a systematic review and meta-analysis of the literature on existing surgical treatments of OO to assess the safety and efficacy of surgical treatments of OO and to evaluate the surgical options for different locations of OO. Methods: The inclusion criteria in the literature are 1. Patients diagnosed as osteoid osteoma and treated surgically ; 2. Include at least five patients ; 3. Perioperative Visual analogue scale ( VAS ), postoperative complications and recurrence were recorded ; 4. Literatures available in PubMed from January 2014 to December 2021. Results: The results of Kruskal-Wallis examination of each experimental index in this experiment were clinical success rate H=14.818, p=0.002, postoperative short-term VAS score H=212.858, p<0.001, postoperative long-term VAS score H=122.290, p<0.001, complication rate H=102.799, p<0.001, recurrence rate H=17.655, p<0.001, according to the test criteria of α=0.05, H0 was rejected. The overall means of the outcome index in each group were not completely equal. Conclusion: Percutaneous ablation and open surgery are safe and reliable for OOs, and technical success rate of percutaneous ablation is higher than that of open surgery. Open surgery and cryoablation can be selected for OO close to the nerve and atypical sites, while radiofrequency ablation and microwave ablation can be selected for OOs in most other sites.